Mitochondrial dysfunction-driven AMPK-p53 axis activation underpins the anti-hepatocellular carcinoma effects of sulfane sulfur - Xue Zheng; Yuhua Luo; Rui Huo; Yiwen Wang; Youbang Chen; Mianrong Chen; Qi Zhao; Kexin Li; Hanyi Zhang; Xiaotong Li; Xiang Li; Hui Zhang; et al. (Scientific Reports)
Abstract Hepatocellular carcinoma (HCC) is the most prevalent form of primary liver cancer, notoriously refractory to conventional chemotherapy. Historically, sulfane sulfur-based compounds have been explored for the treatment of HCC, but their efficacy has been underwhelming. We recently reported a novel sulfane sulfur donor, PSCP, which exhibited improved chemical stability and structural malleability. This study aimed to investigate the effects of PSCP on HCC and elucidate the underlying mechanisms. We utilized bioinformatics algorithms for clustering, function enrichment, feature screening and survival analysis on proteomic data from the Cancer Proteome Atlas (CPTAC) and transcriptomic data from the Cancer Genome Atlas (TCGA). The impact of PSCP on HCC was assessed in vitro and in vivo, focusing on the expression and activity of p53 and AMP-activated protein kinase (AMPK), as well as mitochondrial function. The molecular target of PSCP was identified using Autodock, and binding interactions were visually analyzed. Sulfur metabolism was found to be reprogrammed in HCC, with downregulation of sulfur-related pathways correlating with poor patient prognosis. PSCP treatment significantly inhibited HCC tumor growth in an allograft model, reduced cell viability and proliferation, and induced apoptosis. PSCP potently increased p53 expression and induced AMPK phosphorylation in SNU398 HCC cells. AMPK suppression diminished PSCP-induced p53 upregulation. PSCP also impaired mitochondrial function by inhibiting mitochondrial respiratory complex I, with Ndus3 likely being the target of PSCP’s action. Supplementation with ATP significantly countered PSCP-induced SNU398 cell injury. Our findings suggest that the reprogramming of sulfur-related metabolic pathways is pivotal in HCC. PSCP presents as a promising therapeutic strategy by activating the AMPK-p53 signaling axis.